A produção textual escrita na EJA: uma análise a partir dos estudos da análise crítica do discurso - Ruotti, William (2008)
This work intended to talk about the posture of the Portuguese teacher while developing activities in the writing classes, in particular, in classrooms of high schools of the Youth and Adult Education (YAE). Today, it is said very in the knowledge that the student, in activities of writing, must possess to constitute its text of direction. In this scene, its important to comprehend the paper and the work of the professor to develop activities where the writing become one significant practice. Thus, the objetive was to demonstrate that the teacher, knowing the writing class as social event and the text produced by the student like a moment of this event, can establish with bigger security the ways for the teaching and learning of the written production. In order to develop this investigation, the studies of the Critical Discourse Analysis will provide to one better agreement of the dynamics of relations between speech and society, reproduction of power and social inaquality, inherent to the school, the lessons of writing and its especificidades. The CDA, considering the linguistic in the social interior, where the understanding of the social and psychological construction of the individuals is basic, demonstrate that the practice of writing in the school are not practices without historical and social context, but yes inserted in discourse and social practice of accomplishment. With the analyses was possible to understand the form how a student/author acts, represent the world and identify oneself inside text; this way of seeing the written production is what will allow to a teacher a clear and solid work of the writing competences and skills